2019
DOI: 10.1590/1982-0275201936e180026
|View full text |Cite
|
Sign up to set email alerts
|

Jealousy and anxiety in male domestic abusers: A comparative study

Abstract: The present study aimed at investigating the relationship between partner’s jealousy and the anxiety level presented by male domestic abusers, comparing these variables with men of similar age, socio-economic status, and educational level, without a history of domestic violence. The sample consisted of 20 male abusers and 20 men without a history of violence towards their partner. A Batterer Semi-Structured Interview on Family of Origin; the Romantic Jealousy Scale; and the Beck Anxiety Inventory were used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Among the types of violence, psychological aggression is the most difficult to identify and situations of aggression of this type can occur for a long time, causing emotional impact (Colossi, Marasca & Falcke, 2015), such as anxiety, depression, and impulsivity (Costa, 2010;Priolo Filho et al, 2019), which may even lead to the occurrence of suicide (Secretaria de Políticas de Saúde, 2001). In addition to direct combating situations of violence in love relationships, attention should also be paid to the origins of violent behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Among the types of violence, psychological aggression is the most difficult to identify and situations of aggression of this type can occur for a long time, causing emotional impact (Colossi, Marasca & Falcke, 2015), such as anxiety, depression, and impulsivity (Costa, 2010;Priolo Filho et al, 2019), which may even lead to the occurrence of suicide (Secretaria de Políticas de Saúde, 2001). In addition to direct combating situations of violence in love relationships, attention should also be paid to the origins of violent behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the jealousy felt is normal or morbid is often not crucial; an individual's other characteristics, such as impulsiveness and insensitivity, are the main factors that lead to violence (Mullen, 1995). Filho et al (2019) suggested that jealousy combined with anxiety may contribute to IPV. Love can cause people to become victims of emotional abuse; if they love the wrong person, love will be the source of hurt or suffering, heartbreak, and regret (Milligan, 2011), or they might find it difficult to differentiate between their emotions or distinguish between the types of love, including unconditional, sexual, and mature love.…”
Section: Discussionmentioning
confidence: 99%